Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/jf504394h
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Components of Hard Resin in Hops (Humulus lupulus L.) and Structural Elucidation of Their Transformation Products Formed during the Brewing Process

Abstract: The resins from hops (Humulus lupulus L.), which add the bitter taste to beer, are classified into two main sub-fractions, namely, soft and hard resins. α- and β-Acids in soft resin and their transformation during the wort boiling process are well-studied; however, other constituents in resins, especially hard resin, have been unidentified. In this study, we identified humulinones and hulupones as soft-resin components, in addition to 4'-hydroxyallohumulinones and tricyclooxyisohumulones A and B as hard-resin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
(72 reference statements)
2
34
2
Order By: Relevance
“…In contrast, oxidation of α-and β-acids produces bitter acid oxides, such as matured hop bitter acids (MHBA). All of the structurally elucidated compounds of MHBA possess a common β-tricarbonyl moiety similar to α-, β-, and isoα-acids (Taniguchi et al, 2013(Taniguchi et al, , 2014a(Taniguchi et al, , 2014b(Taniguchi et al, , 2015. We demonstrated that MHBA suppresses diet-induced body fat accumulation in animals (Morimoto-Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, oxidation of α-and β-acids produces bitter acid oxides, such as matured hop bitter acids (MHBA). All of the structurally elucidated compounds of MHBA possess a common β-tricarbonyl moiety similar to α-, β-, and isoα-acids (Taniguchi et al, 2013(Taniguchi et al, , 2014a(Taniguchi et al, , 2014b(Taniguchi et al, , 2015. We demonstrated that MHBA suppresses diet-induced body fat accumulation in animals (Morimoto-Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 76%
“…33) 4′-Hydroxyallohumulinones (6a-c), 4′-hydroxyallo-cis-cohumulinone (7a), 4′-hydroxyallo-cis-n-humulinone (7b), cis-oxycohumulinic acid (8a), and cis-oxy-n-humulinic acid (8b) were isolated in our laboratory. 34) Preparation of a MHBA fraction from stored hops. Hop pellets (600 g) were stored at 60°C for 120 h to oxidize αand β-acids and then extracted with prewarmed H 2 O (50°C, 6 L) for 1 h. During extraction, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Next, an aqueous solution of the extract was heated. The heating process induced chemical reactions that occur during the wort boiling process, such as transformation of unstable 4′-hydroxyallohumulinones (6a-c) into 4′-hydroxyallo-cis-humulinones (7a-c) and cis-oxyhumulinic acids (8a-c), 34) as well as potentially other reactions, resulting in the stabilization of the composition of the extract (Fig. 2D).…”
Section: Mhba Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Alternatively, the cataloguing can be conducted according to their solubility in specific solvents: spirit soluble (shellac, rosin, sandarac); turpentine soluble (dammar and mastic); and oil soluble (copal from Congo).…”
mentioning
confidence: 99%